THE TRADE OF PINHÃO (Araucaria angustifolia SEED) IN MINAS GERAIS: A STIMULUS FOR CONSERVATION? - Marques, Ricardo Tayarol; Barros, Vanessa Cabral Costa de; Borges, Luís Antonio Coimbra; Barbosa, Ana Carolina Maioli Campos (Floresta, 2021)
The knowledge of the production and marketing chains of pinhão is centered in the Mixed Ombrophilous Forest region, in southern Brazil. This study aimed to evaluate the pinhão production and marketing chains in a region of ecological tension (Seasonal Semideciduous Forest) and verify the pinhão trade effectiveness as a tool for araucaria conservation. This research was based on a statistical survey on pinhão extraction and trade, made available by governmental institutions. To identify establishments operating in the trade of pinhão in Minas Gerais (Brazil), structured interviews and a literature review of the legislation associated with the trade of forest products were conducted, establishing the relationship between the trade and conservation of araucaria. The results showed that Minas Gerais is the third-largest national producer of pinhão, accounting for 13.9% of production, and receiving the lowest remuneration for the extracted product. There is a predominance of a short marketing chain, in which producers or retailers negotiate with the consumer, resulting in greater profits for those involved in this process, who benefit from the lack of specific regulations and inspections in the extraction and trade of pinhão, leading to a predatory activity, which does not contribute to the preservation of araucaria. However, the use of appropriate instruments may make feasible the conservation of this species, combining its potential for use in forest restoration projects with the income from the commercialization of its seeds, thus developing an effective tool for the conservation of araucaria in rural properties in Minas Gerais.